A= first number
B= second number
C= third number
A + B + C
Then divide by 5
Answer: it has no solution
Step-by-step explanation:
First step is to do distributive property.
so you multiply 5 by -3.4k and -7
your equation now is -17k-35+(3k+21)
Then you add like terms
add -17k+3k to give you -14k-35+21
then you add like terms again
add -35+21 to give you -14
so now your equation is -14k-14
So that is your answer simplified
<span>–6(x – 2y) when x = –3 and y = –5
so
</span><span>–6(x – 2y)
= </span><span>–6(-3 – 2(-5))
= -6(-3 + 10)
= -6(7)
= -42
answer
</span><span>A. -42</span>
Answer:
The answer is y = StartFraction 15 Over 22 EndFraction x + StartFraction 6 Over 11 EndFraction → y = 15/22x + 6/11